FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN METODE KONTRASEPSI JANGKA PANJANG (MKJP) PADA AKSEPTOR KB AKTIF DI WILAYAH KERJA PUSKESMAS SUNGAILIAT KABUPATEN BANGKA (Program Studi Ilmu Kesehatan STIKESÂ Abdi Nusa Pangkalpinang, 2021)
The objective of family-planning program are population growth control and an increase of high quality small size family. The increasement and growth of population amount can raise a number of problem, such as lack of food and nutrition thus lead to poor community health, low education, lack of employment, a high level of pregnancy and death especially in a developing country. The purpose of this research is to understand factors related to selection of long term contraception method towards active family-planning acceptors in the work area of Sungailiat public health center in Bangka District. This research used analytical survey with case control method, the subject in this research is active family-planning acceptor with a total sample of 196 people consisted of 98 cases and 98 controls. Data were collected with the support of questionnaire and direct interview using Purposive Sampling technique for both case samples and control samples, which is a data source collection technique with certain considerations.The result of this research shows that factors related to selection of long term contraception method on active family planning acceptors in the work area of Sungailiat public health center in Bangka District in 2019 is knowledge (p=0.001), attitude (p=0.000), source of information (p=0.000) and partner support (p=0.003) while the dominant factor is source of information (OR=3.486).